Integration of environmental problems into economic analyses of state policy of the Republic of Kazakhstan - Yemelina, N.K.; Assanova, M.A.; Yugay, S.V. (BUKETOV BUSINESS REVIEW, 2019)
Nowadays, regulation of water resources consumption is one of the most important task of economic policy in Kazakhstan. Special attention in this problem is paid to the effective use of water in agriculture because this sector is the biggest consumer of water in the country. From the standpoint of the New Public Management methodology the authors examine the implementation of project management tools in regulating environmental policy in Kazakhstan. The focus is done on management of water resources. Within the framework of project management authors tried to measure sustainable regional development. Environmental problems in sphere of water resources management are reflected in the calculation of some indicators for measuring sustainable development of a country. In particular, the authors study the issues of Sustainable Society Index. Based on the analysis and research of the problem areas in ecological management of Kazakhstan, the study attempts to solve theoretical and practical problems of increasing the effectiveness of public management of the region’s environmental development.